Teaching Residents How to Talk About Death and Dying: A Mixed-Methods Analysis of Barriers and Randomized Educational Intervention. (September 2018) - Miller, David C.; Sullivan, Amy M.; Soffler, Morgan; Armstrong, Brett; Anandaiah, Asha; Rock, Laura; McSparron, Jakob I.; Schwartzstein, Richard M.; Hayes, Margaret M.
Objectives: We present a pilot study exploring the effects of a brief, 30-minute educational intervention targeting resident communication surrounding dying in the intensive care unit (ICU). We sought to determine whether simulation or didactic educational interventions improved resident-reported comfort, preparation, and skill acquisition. We also sought to identify resident barriers to using the word "dying." Methods: In this mixed-methods prospective study, second- and third-year medical residents were randomized to participate in a simulation-based communication training or a didactic session. Residents completed a pre–post survey after the sessions evaluating the sessions and reflecting on their use of the word "dying" in family meetings. Results: Forty-five residents participated in the study. Residents reported increases in comfort (Mean [M]-pre = 3.3 [standard deviation: 0.6], M-post = 3.7 [0.7]; P < .01, Cohen d = 0.75) and preparation (M-pre = 3.4 [0.7], M-post = 3.9 [0.6]; P < .01, d = 1.07) using the word "dying" after both the simulation and didactic versions. Residents randomized to the simulation reported they were more likely to have learned new skills as compared to residents in the didactic (M-simulation = 2.2 [0.4], M-didactic = 1.9 [0.3]; P = .015, d = 0.80). They estimated that they used the word "dying" in 50% of their end-of-life (EOL) conversations and identified uncertain prognosis as the main barrier to explicitly stating the word "dying." Conclusion: A 30-minute educational intervention improves internal medicine residents' self-reported comfort and preparation in talking about death and dying in the ICU. Residents in simulation-based training were more likely to report they learned new skills as compared to the didactic session. Residents report multiple barriers to using the word "dying" EOL conversations.